Adherence to and Invasion of Host Cells by Spotted Fever Group Rickettsia Species - Chan, Yvonne G.; Riley, Sean P.; Martinez, Juan J. (Frontiers in Microbiology, 2010)
The pathogenic lifecycle of obligate intracellular bacteria presents a superb opportunity to develop understanding of the interaction between the bacteria and host under the pretext that disruption of these processes will likely lead to death of the pathogen and prevention of associated disease. Species of the genus Rickettsia contain some of the most hazardous of the obligate intracellular bacteria, including Rickettsia rickettsii and R. conorii the causative agents of Rocky Mountain and Mediterranean spotted fevers, respectively. Spotted fever group Rickettsia species commonly invade and thrive within cells of the host circulatory system whereby the endothelial cells are severely perturbed. The subsequent disruption of circulatory continuity results in much of the severe morbidity and mortality associated with these diseases, including macropapular dermal rash, interstitial pneumonia, acute renal failure, pulmonary edema, and other multisystem manifestations. This review describes current knowledge of the essential pathogenic processes of adherence to and invasion of host cells, efforts to disrupt these processes, and potential for disease prevention through vaccination with recently identified bacterial adherence and invasion proteins. A more complete understanding of these bacterial proteins will provide an opportunity for prevention and treatment of spotted fever group Rickettsia infections.